2005
DOI: 10.1002/pds.1156
|View full text |Cite
|
Sign up to set email alerts
|

Differences in antihypertensive drug persistence associated with drug class and gender: a PHARMO study

Abstract: These results demonstrate marked differences in persistence between AHT classes, with the highest persistence for ARBs and lowest for diuretics. Women were less persistent with their AHT compared to men. This low persistence leads to suboptimal treatment with a potential for substantial clinical consequences. Especially in women, more attention paid to AHT persistence patterns could improve their cardiovascular outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 29 publications
(39 reference statements)
8
41
2
2
Order By: Relevance
“…In agreement with other reports, [22][23][24][25][26] in our setting, more than 55% of patients had already discontinued treatment after 1 year since starting therapy. Poor socioeconomic status has been found to be related to the lack of adherence in antihypertensive drugs in previous studies.…”
Section: Discussionsupporting
confidence: 81%
“…In agreement with other reports, [22][23][24][25][26] in our setting, more than 55% of patients had already discontinued treatment after 1 year since starting therapy. Poor socioeconomic status has been found to be related to the lack of adherence in antihypertensive drugs in previous studies.…”
Section: Discussionsupporting
confidence: 81%
“…15 In addition, compliance is known to be low on diuretics and the tendency to induce type II diabetes is well-documented. 8,16 In our study men more often received ACE inhibitors compared with women. Men also had a higher prevalence of diabetes mellitus at baseline and this could explain the more frequent use of ACE inhibitors.…”
Section: Discussionmentioning
confidence: 53%
“…17 The highest persistence has been shown in patients using ARBs. 8 In our study the use of ARBs was unusually high and it cannot be ruled out that this could have contributed to the high rate of patients reaching target blood pressure. However, more than two-thirds of the participating sites were owned by private practitioners and this could also explain the high degree of prescriptions of ARBs because primary health care centres within the regular social security system possibly were more adherent to recommendations by the Medical Products Agency in Sweden where diuretics, calcium channel blockers and ACE inhibitors are recommended as first line antihypertensive therapy.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Thirty-nine studies (22 new, including three evaluating a DRI) reported at least some quantitative information on persistence or adherence. 11,13,14,16,26,30,36,37,[42][43][44]47,48,50,55,57,58,62,73,76,81,88,89,[93][94][95]97,98,[106][107][108][109][110][111][112][113][114][115][116][117][118] Adherence to study protocol, in terms of pill counts, was universally high: at least 97% in five of the nine studies assessed and above 90% in all nine, without significant between group differences. Persistence with ARBs was modestly better than with ACE inhibitors, primarily due to adverse effects.…”
Section: Serum Creatinine Level Glomerular Filtration Rate and Protmentioning
confidence: 99%